Evaluating the knowledge, roles, and skills of health cadres in stunting prevention: A mixed-method study in Indonesia - Widiasih, Restuning; Sunjaya, Deni Kurniadi; Rahayuwati, Laili; Rusyidi, Binahayati; Ermiati; Sari, Citra Windani Mambang; Mardani; Rusdi; Tung, Serene En Hui (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Stunting remains a critical public health issue in Indonesia, threatening the well-being of future generations. Community involvement, particularly by health cadres, is essential for effective prevention. However, structured assessments and follow-up initiatives to enhance their participation remain limited. Objective: This study aimed to evaluate health cadres' knowledge, roles, and skills in stunting prevention programs. Methods: A mixed-methods design with an embedded approach was applied in three phases. Phase 1: A quantitative survey assessed stunting knowledge among 193 cadres across 10 stunting locus villages in Bangka Belitung Province, Indonesia (October–December 2022). The survey tool was adapted from previous studies and analyzed using the RASCH IRT model and descriptive statistics. Phase 2: Qualitative data were collected through semi-structured interviews with 20 cadres selected from the survey pool, and analyzed thematically. Phase 3: The same 20 cadres were observed conducting anthropometric measurements to assess skill accuracy. Results: Knowledge levels were generally low, with 52% of cadres scoring low to very low and only 48% achieving moderate to high scores. Three themes emerged: 1) cadres’ perspectives on the causes and consequences of stunting, 2) their roles and actions in stunting prevention, and 3) their experiences during the COVID-19 pandemic. Observations revealed significant inaccuracies in anthropometric measurement techniques. Conclusion: There is a clear need to improve cadres’ knowledge and skills, especially in anthropometric assessment. Recommendations include implementing certification-based training, introducing innovative and standardized measurement tools, and offering accessible web-based learning platforms. Nurses play a crucial role in supporting cadre training and ensuring accurate growth monitoring at the community level.